In vitro propagation of Salvia sclarea L. by meta-Topolin, and assessment of genetic stability and secondary metabolite profiling of micropropagated plants - Erisen, Semiha; Kurt-Gur, Gunseli; Servi, Huseyin (ELSEVIER, 2020)
The influence of meta-Topolin (mT) on micropropagation of Salvia sclarea L. (clary sage) was compared with N6-benzylaminopurine (BAP), kinetin (KIN) and thidiazuron (TDZ). mT was superior over all other cytokinin for not only shoot regeneration but also rooting. The highest shoot number (4.9 shoots/explants) was noted on nodal segments cultured on Murashige and Skoog (MS) medium including 2.0 mg/L mT and 0.2 mg/L indole-3-acetic acid (IAA). The regenerated shoots derived from mT including medium were rooted successfully on MS medium having 1.0 mg/L 1-naphthaleneacetic acid (NAA). Plantlets were successfully acclimatised (100%) and exhibited vigorous development in the greenhouse. The genetic stability of the propagated plants was assessed by start codon targeted polymorphism (SCoT) primers. A total variability of 3.13% was noted in the regenerants that revealed a high rated of genetic stability among the micropropagated plants. In addition, the secondary metabolite profiling of micropropagated plants was evaluated with gas chromatography-mass spectrometry (GC-MS). Although the hexane extracts of plants were dominated by n-alkanes, cytokinins added in the culture media altered their secondary metabolite contents. The protocol described here is a rapid and reliable micropropagation protocol for large-scale production of clonally stable clary sage plants for commercial purposes.
Keywords: Clary sage; Cytokinins; Micropropagation; Somaclonal variation; ESSENTIAL OILS; AROMATIC CYTOKININ; SHOOT; REGENERATION; BENZYLADENINE; PROTOCOL; CULTURE; GROWTH; LEAVES; Agriculture